Gênero e a saúde do assistente social que atua nos centros de referência especializados para pessoa em situação de rua - Carvalho, Letícia Alves (2023)
The present work proposes to analyze the theme of gender in Social Work, focusing on the working conditions of professional social workers who work in a Specialized Center for Homeless People, in the city of Uberlândia/MG. It aims to demonstrate to what extent the construction of gender has implications for the work, physical and mental health of these professionals, especially in light of the illness/mental suffering of these workers. It starts from the understanding of the importance of this approach, by presenting numerous implications of gender conditions in the work relationships of social workers, such as unstable, exhausting and precarious employment relationships, whose implications reflect on the worker's subjectivity, their physical and psychic and in their process of becoming ill through work. The dialectical method was used, with a quantitative, qualitative and descriptive approach, being approved by the Ethics Committee under nº 63960822.0.0000.5152. As a thematic analysis technique, theoretical saturation was used and the research was carried out in stages, the first consisting of the application of a questionnaire, the second, the application of a semi-structured interview and the last, the analysis and discussion of the results. To this end, the IramuteQ software and Thematic Analysis in Bardin were used. The result is that all interviewees are female and claim that the work environment generates illness, especially in relation to mental health. It is possible to conclude that there is an intense compromise in the health of social worker workers combined with gender issues.